(untitled) (Englisia : Journal of Language, Education, and Humanities, 2025)
The integration of Online Machine Translation (OMT) into English as a Foreign Language (EFL) classrooms has ignited discussions about its practical use and ethical implications, particularly in Islamic universities where academic integrity is a core value. This study investigates the role of OMT in language instruction, explores Indonesian EFL learners’ perspectives on its use, and identifies strategies to address the challenges it presents. Employing a qualitative case study approach, data were gathered through classroom observations, semi-structured interviews with three students and two lecturers selected via purposive sampling, and document analysis. Thematic analysis was used to interpret the findings. Results reveal that OMT enhances students’ vocabulary, serves as a writing aid, and supports speaking practice in the language classroom. It offers benefits such as time efficiency, valuable features, and user convenience. However, challenges including inaccuracies, mistranslations, over-reliance, and excessive dependency were also evident. Both students and lecturers proposed strategies to mitigate these issues, such as fostering awareness of academic integrity among Islamic university students and restricting OMT use in classroom settings.